Modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, flame-retardant low-smoke oil-resistant TPE (Thermoplastic Elastomer) sheath material, preparation method of flame-retardant low-smoke oil-resistant TPE sheath material and sheath prepared from TPE sheath material

By using modified nano-aluminum hydroxide/hexagonal boron nitride nanocomposite powder and organic flame retardants in cable sheath materials, the problems of insufficient low-smoke flame retardant performance and oil resistance of existing materials are solved, and high efficiency is achieved. Improved flame retardant and oil resistance properties.

CN119331311APending Publication Date: 2025-01-21SHENZHEN WOER HEAT SHRINKABLE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411212058.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The low smoke flame retardant and oil resistance of existing cable sheath materials are insufficient, resulting in the cable being oil-resistant and mechanical properties.

Method used

Modified nano-aluminum hydroxide/hexagonal boron nitride nano-composite powder is used, synthesized through solution method, and combined with organic flame retardants to prepare flame-retardant, low-smoke and oil-resistant TPE sheathing materials.

Benefits of technology

It improves the flame retardant ability and oil resistance of the sheath material, achieves low-smoke, halogen-free and efficient flame retardancy, and enhances the mechanical properties and flame retardant properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder. The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is prepared from at least hexagonal boron nitride, isopropanol, aluminum chloride hydrate, n-butyl alcohol, ammonia water and a silane coupling agent. The flame-retardant low-smoke oil-resistant TPE sheath material provided by the invention has good oil resistance and high flame retardance, and is suitable for the cable industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electric wires and cables, and in particular to a modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, a sheath material and a preparation method thereof, and a sheath. Background Art

[0002] In the cable industry, the choice of sheath material is crucial to the performance and service life of the cable. Thermoplastic elastomers have some excellent properties of rubber and plastic, and also have the characteristics of a wide range of hardness, soft touch, and good weather resistance. These advantages make TPE one of the preferred sheath materials for modern wires and cables. Therefore, it has been widely used in new energy charging cables, industrial drag chain lines and other scenes. At present, the basic characteristics of TPE sheath materials on the market are mainly low-smoke halogen-free flame retardant. The halogen-free flame retardants on the market are mainly phosphorus flame retardants, silicon flame retardants, inorganic metal flame retardants and bio-based flame retardants, etc. However, single-component halogen-free flame retardants face the problems of large addition amount, lower flame retardant effect than halogen-containing flame retardant, and the cable is not oil-resistant and has insufficient mechanical properties. Therefore, it is necessary to develop an efficient low-smoke halogen-free flame retardant and oil-resistant solution and low-smoke halogen-free flame retardant and oil-resistant TPE sheath material. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder, a flame retardant, low-smoke and oil-resistant TPE sheath material, a preparation method and a sheath made from the TPE sheath material, aiming to solve the problem of insufficient low-smoke flame retardant performance and oil resistance of current cable sheath materials.

[0004] To achieve the above-mentioned purpose, the present invention proposes a modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder, a flame retardant, low smoke and oil resistant TPE sheath material, a preparation method and a sheath made from the TPE sheath material. A modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder, wherein the modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder is synthesized by a solution method from hexagonal boron nitride, isopropyl alcohol, aluminum chlorohydrate, n-butanol, ammonia water and a silane coupling agent.

[0005] Optionally, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0006] A flame retardant, low smoke and oil resistant TPE sheath material, wherein the ingredients of the flame retardant, low smoke and oil resistant TPE sheath material are measured by weight and include: 15-30 parts of thermoplastic elastomer; 3-15 parts of polypropylene; 5-30 parts of white oil; 3-10 parts of the above-mentioned modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; 5-10 parts of polyolefin elastomer; and 10-20 parts of organic flame retardant.

[0007] Optionally, the white oil is at least one of 40#-300# industrial white oils.

[0008] Optionally, the polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer and ethylene-octene copolymer.

[0009] Optionally, the organic flame retardant is at least one of a phosphorus-based flame retardant, a nitrogen-based flame retardant and a silicon-based flame retardant.

[0010] Optionally, the flame-retardant, low-smoke, and oil-resistant TPE sheath material further includes 0.5-2 parts of a lubricant and 0.4-1 parts of an antioxidant, wherein the lubricant is at least one of fatty acids, aliphatic amides, metal soaps, and fatty alcohols, and the antioxidant is bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetra(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5 -tolyl] 2,4,8,10-tetraoxaspiro[5,5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)ester), 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicylamidophthalimide.

[0011] In order to achieve the above-mentioned purpose, the present invention also proposes a method for preparing a flame-retardant, low-smoke and oil-resistant TPE sheath material, comprising the following steps: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method from the above-mentioned hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water and silane coupling agent; preparing flame-retardant, low-smoke and oil-resistant TPE sheath material: pre-mixing thermoplastic elastomer, polypropylene, white oil, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, polyolefin elastomer, organic flame retardant, lubricant and antioxidant uniformly, and then mixing them in an internal mixer to prepare a molten blend, and granulating the molten blend in a twin-screw-single-screw hot-cut air-cooled granulation unit, followed by secondary air cooling and vibration screening, and finally obtaining a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0012] Optionally, the preparation method of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: exfoliating hexagonal boron nitride to form hexagonal boron nitride nano sheets and hydroxylating the sheets to obtain micro-nano hexagonal boron nitride powder, then in situ growing nano aluminum hydroxide on the surface of the micro-nano hexagonal boron nitride powder to obtain nano aluminum hydroxide / hexagonal boron nitride nano composite powder, then adding the nano aluminum hydroxide / hexagonal boron nitride nano composite powder and a silane coupling agent to an ethanol solution, and drying after ultrasonic dispersion and vacuum filtration to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder.

[0013] In order to achieve the above object, the present invention further provides a TPE sheath, which is prepared by any one of the above-mentioned preparation methods of the flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0014] Beneficial effects of the present invention: In the present invention, by synthesizing modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder, the hexagonal boron nitride is subjected to exfoliation and hydroxylation to obtain modified hexagonal boron nitride nanosheets, whose sheet structure can effectively improve the oil resistance of the matrix; and the nano-aluminum hydroxide generated in situ on its surface has a large specific surface area, which reduces the partial pressure of water vapor on the particle surface, and can improve the flame retardant effect to a certain extent. In addition, due to the excellent thermal conductivity and thermal stability of hexagonal boron nitride, it can improve the heat resistance of nano-aluminum hydroxide, so the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression, and the use of compound with organic flame retardant can reduce its dosage and achieve excellent flame retardant effect.

[0015] The present invention also uses the above-mentioned modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder to prepare a flame-retardant, low-smoke, and oil-resistant TPE sheath material. Thermoplastic elastomer, polypropylene, white oil, polyolefin elastomer, and organic flame retardant are mixed together as a mixed elastomer component of the flame-retardant, low-smoke, and oil-resistant TPE sheath material. By adding the modified nano aluminum hydroxide / hexagonal boron nitride nano-composite powder, not only the oil resistance of the substrate can be improved, but also the flame retardant ability of the sheath material can be improved, and the flame retardant effect can be improved, thereby realizing the composite modification of the flame-retardant, low-smoke, and oil-resistant TPE sheath material, so that it obtains excellent flame retardant and oil-resistant properties. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0017] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.

[0018] In order to facilitate the understanding of this embodiment, the symbols, instruments and terms are explained below: TPE: Thermoplastic Elastomer, a type of elastomer that has the elasticity of rubber at room temperature and can be plasticized and molded at high temperatures. The structural characteristics of thermoplastic elastomers are that they are composed of different resin segments and rubber segments composed of chemical bonds. The resin segments form physical crosslinking points by virtue of the interchain forces, and the rubber segments are highly elastic segments that contribute to elasticity. The physical crosslinking of the plastic segments changes reversibly with changes in temperature, showing the plastic processing characteristics of thermoplastic elastomers.

[0019] In the cable industry, cross-linked polyolefin materials are widely used due to their excellent electrical properties and good mechanical strength. Although cross-linked polyolefin occupies an important position in cable applications, it still has some performance limitations. First, the flame retardancy of cross-linked polyolefin materials is not enough to meet certain strict safety standards. Second, the lack of scratch resistance of cross-linked polyolefin materials may cause sheath damage and shorten the service life of the cable. Therefore, there is an urgent need for a cable with strong scratch resistance and high flame retardancy to keep its electrical properties unaffected.

[0020] To solve the above problems, the present invention provides a modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, characterized in that the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder is synthesized by a solution method from hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent.

[0021] In the present invention, modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder is synthesized by solution method, and hexagonal boron nitride is subjected to exfoliation and hydroxylation to obtain modified hexagonal boron nitride nanosheets, whose sheet structure can effectively improve the oil resistance of the matrix; and the nano aluminum hydroxide generated in situ on its surface has a large specific surface area, which reduces the partial pressure of water vapor on the particle surface, and can improve the flame retardant effect to a certain extent. In addition, due to the excellent thermal conductivity and thermal stability of hexagonal boron nitride, it can improve the heat resistance of nano aluminum hydroxide, so the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression, and the use of organic flame retardants in combination can reduce its dosage and achieve excellent flame retardant effect.

[0022] Furthermore, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0023] In some embodiments, the silane coupling agent is preferably 3-aminopropyltriethoxysilane.

[0024] The present invention also proposes a flame-retardant, low-smoke, and oil-resistant TPE sheath material, characterized in that the ingredients of the flame-retardant, low-smoke, and oil-resistant TPE sheath material, measured in parts by weight, include: 15-30 parts of thermoplastic elastomer; 3-15 parts of polypropylene; 5-30 parts of white oil; 3-10 parts of the above-mentioned modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; 5-10 parts of polyolefin elastomer; and 10-20 parts of organic flame retardant.

[0025] In some embodiments, the ingredients of the flame retardant, low smoke and oil resistant TPE sheath material, measured in parts by weight, preferably include: 15-30 parts of thermoplastic elastomer; 3-15 parts of polypropylene; 5-30 parts of white oil; 3-10 parts of the above-mentioned modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder; 5-10 parts of polyolefin elastomer; and 10-20 parts of organic flame retardant.

[0026] Furthermore, the thermoplastic elastomer is at least one of a styrene ethylene / butylene block copolymer and a hydrogenated styrene isoprene hydroxystyrene copolymer.

[0027] In some embodiments, the thermoplastic elastomer is preferably a styrene ethylene / butylene block copolymer.

[0028] Furthermore, the white oil is at least one of 40#-300# industrial white oils. In some embodiments, the white oil is preferably 40# white oil.

[0029] Further, the polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer and ethylene-octene copolymer.

[0030] In some embodiments, the polyolefin elastomer is preferably ethylene-methyl acrylate copolymer.

[0031] In some embodiments, the polyolefin elastomer is preferably a mixture of ethylene-butene copolymer and ethylene-octene copolymer.

[0032] Furthermore, the organic flame retardant is at least one of a phosphorus-based flame retardant, a nitrogen-based flame retardant and a silicon-based flame retardant.

[0033] In some embodiments, the organic flame retardant is at least one of tris(2,3-dibromopropyl) phosphate and tris(monochloropropyl) phosphate.

[0034] Furthermore, the flame-retardant, low-smoke and oil-resistant TPE sheath material also includes 0.5-2 parts of lubricant and 0.4-1 parts of antioxidant, the lubricant is at least one of fatty acids, aliphatic amides, metal soaps and fatty alcohols, and the antioxidant is bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetra(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5-methylphenyl]2,4,8,10-tetraoxaspiro[5,5]undecane-3,9-diylbis(2-methylpropane-2, At least one of 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicylamide phthalimide. The lubricant can improve the fluidity during processing, increase the impact strength of the material, reduce the water absorption of the cable surface, improve cable scratches and surface defects, and reduce the heat release rate and smoke generation, all of which help to improve the performance and safety of the cable. The addition of antioxidants can prevent thermal oxidative degradation of the elastomer, and can improve the heat resistance, aging resistance, electrical properties and mechanical properties of the material.

[0035] In some embodiments, the lubricant is preferably 0.5 parts of a fatty acid-based lubricant.

[0036] In some embodiments, the antioxidant is preferably 0.5 parts of bis(octadecyl)hydroxylamine.

[0037] In order to solve the above problems, the present invention also proposes a method for preparing a flame-retardant, low-smoke and oil-resistant TPE sheath material, comprising the following steps: S1: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using the above-mentioned hexagonal boron nitride, isopropyl alcohol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; In this scheme, the hexagonal boron nitride in the modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder is treated to obtain a micro-nano hexagonal boron nitride, which has the characteristics of both nanomaterials and micron fillers. First, the micron sheet filler can improve the scratch resistance of the matrix due to the low friction coefficient of hexagonal boron nitride itself; secondly, the structure of the nanosheet makes the subsequent growth of nano-aluminum hydroxide, and the specific surface area of ​​the nano-aluminum hydroxide generated in situ on the surface of the hexagonal boron nitride nanosheet is large, which reduces the partial pressure of water vapor on the particle surface, and can improve the flame retardant effect to a certain extent. In addition, due to the excellent thermal conductivity and thermal stability of hexagonal boron nitride, it can improve the heat resistance of nano-aluminum hydroxide, so the combination of the two has the characteristics of synergistic flame retardancy and smoke suppression, and the use of flame retardants in combination can reduce its dosage and achieve excellent flame retardant effects. Finally, the sheet structure of micro-nano hexagonal boron nitride can also change the path of oxygen, moisture, etc. entering the resin matrix, thereby improving the aging resistance.

[0038] S2: preparing flame-retardant, low-smoke and oil-resistant TPE sheath material: pre-mixing thermoplastic elastomer, polypropylene, white oil, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, polyolefin elastomer, organic flame retardant, lubricant and antioxidant, and then mixing them in an internal mixer to prepare a molten blend; In some embodiments, internal mixing is performed in an internal mixer.

[0039] S3: The molten blend is granulated by extrusion, followed by air cooling and screening to finally obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0040] In some embodiments, extrusion granulation is achieved by a twin-screw-single-screw hot-cut air-cooled granulation unit.

[0041] Furthermore, the preparation method of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.

[0042] In some embodiments, hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonicated for 24 hours using an ultrasonic disperser at a power of 500 W. After vacuum filtration, the solution is dried in a vacuum oven at 80-100° C. for 6-8 hours to obtain micro-nano hexagonal boron nitride powder.

[0043] In some embodiments, aluminum chlorohydrate is dissolved in n-butanol solution, and then hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filtration is performed and deionized water is used to wash 5-8 times to wash away Cl-.

[0044] In some embodiments, nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and a silane coupling agent are added to an ethanol solution, ultrasonically dispersed at 40-80°C with a power of 120W for 4 hours, followed by vacuum filtration and drying in a vacuum oven at 70-90°C for 24-30 hours to obtain a modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder.

[0045] Furthermore, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

[0046] In some embodiments, the silane coupling agent is preferably 3-aminopropyltriethoxysilane.

[0047] In order to solve the above problems, the present invention further provides a cable, which is made by the above method for preparing the flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0048] The content of the present invention is explained below through specific examples and data.

[0049] Embodiment 1: The hexagonal boron nitride is peeled off to form hexagonal boron nitride nanosheets and hydroxylated. The hexagonal boron nitride is placed in an isopropanol solution, and then ultrasonically dispersed at 500w for 24 hours, vacuum filtered and dried in a vacuum oven at 80-100℃ for 6-8 hours to obtain micro-nano hexagonal boron nitride powder. Secondly, nano aluminum hydroxide is grown in situ on the surface of hexagonal boron nitride nanosheets. Aluminum chlorohydrate is dissolved in n-butanol solution, and the hexagonal boron nitride nanosheet powder is placed in the solution and stirred evenly, and then ammonia water is quickly poured into the n-butanol solution of aluminum chlorohydrate under vigorous stirring to react for 1-2 hours. After the reaction is completed, vacuum filter again and wash with deionized water 5-8 times to clean Cl - Then, the nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder and the silane coupling agent were added to the ethanol solution, and ultrasonicated at 40-80° C. with a power of 120 W for 4 h using an ultrasonic disperser, followed by vacuum filtration and drying in a vacuum oven at 70-90° C. for 24-30 h, and finally the modified nano aluminum hydroxide / hexagonal boron nitride nanocomposite powder was obtained.

[0050] 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 3 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0051] Embodiment 2: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame retardant, low smoke and oil resistant TPE sheath material.

[0052] Embodiment 3: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 8 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0053] Embodiment 4: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 10 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame retardant, low smoke and oil resistant TPE sheath material.

[0054] Embodiment 5: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 10 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame retardant, low smoke and oil resistant TPE sheath material.

[0055] Embodiment 6: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 20 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame retardant, low smoke and oil resistant TPE sheath material.

[0056] Embodiment 7: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 25 parts of white oil, 10 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 10 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0057] Comparative Example 1: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and then extruded and granulated to obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0058] Comparative Example 2: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 1 part of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0059] Comparative Example 3: The preparation method is the same as that of Example 1, except that: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 13 parts of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain flame retardant, low smoke and oil resistant TPE sheath material.

[0060] Comparative Example 4: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of untreated hexagonal boron nitride, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and extruded into granules to obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0061] Comparative Example 5: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of hydroxylated hexagonal boron nitride, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and then extruded and granulated to obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0062] Comparative Example 6: 25 parts of thermoplastic elastomer, 8 parts of polypropylene, 15 parts of white oil, 5 parts of aluminum hydroxide, 10 parts of polyolefin elastomer, 15 parts of organic flame retardant, 1 part of lubricant and 1 part of antioxidant are mixed and then extruded and granulated to obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

[0063] The components and important preparation variables of Examples 1-7 and Comparative Examples 1-6 are summarized in Table 1.

[0064] Table 1. Components of Examples 1-7 and Comparative Examples 1-6 of the present invention

[0065] According to relevant test standards, the flame retardant, low smoke and oil resistant TPE sheath materials in the above Examples 1-7 and Comparative Examples 1-6 were tested for tensile strength, elongation at break, flame retardant grade and scratch resistance, and the test results were recorded in the following Table 2: Table 2. Performance of Examples 1-7 and Comparative Examples 1-6

[0066] According to the test results above, it can be seen that 5 parts of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder are added in Example 2. The test results show that the tensile strength of Example 2 is 13.8MPa, the elongation at break is 652%, the tensile strength after aging is 89MPa, the elongation at break after aging is 93%, and the flame retardant grade is V-0; 5 parts of untreated hexagonal boron nitride are added in Comparative Example 4. The test results show that the tensile strength is 7.6MPa, the elongation at break is 430%, the tensile strength after aging is 79MPa, the elongation at break after aging is 75%, and the flame retardant grade is V-0. The grade is V-2. By comparing Example 2 and Comparative Example 4, it can be concluded that the tensile strength, elongation at break and flame retardancy of the TPE sheath material added with modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder are higher than those of the TPE sheath material added with 5 parts of untreated hexagonal boron nitride. The TPE sheath material added with modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powder has better mechanical properties and flame retardancy, while untreated hexagonal boron nitride in the matrix will seriously affect the performance of the matrix, resulting in a decrease in its physical and mechanical properties and flame retardancy. In Examples 1-4, the amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder added is gradually increased within the range of 3-15 parts by weight specified in the present invention. In Comparative Examples 1-3, the amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder added is 0 parts, 1 part and 13 parts respectively, which are not within the range of 3-10 parts by weight of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in the present invention. The test results of Comparative Examples 1-4 and Comparative Examples 1-3 show that within the range of 3-10 parts by weight of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder in the present invention, the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder can improve the flame retardant efficiency of the organic flame retardant and reduce the amount of the flame retardant, and within this range, the amount of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder can be increased. As the number of modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders increases, the mechanical properties and flame retardancy of the prepared flame-retardant, low-smoke, and oil-resistant TPE sheath materials are also improved (Examples 1-3); while Comparative Examples 4-6 do not add modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders, 5 parts of untreated hexagonal boron nitride are added in Comparative Example 4, 5 parts of hydroxylated hexagonal boron nitride are added in Comparative Example 5, and 5 parts of aluminum hydroxide are added in Comparative Example 6. It can be concluded from the experimental data that, compared with Example 2 to which modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders are added, the tensile strength, elongation at break, flame retardant grade, and thermal shock resistance of Examples 4-6 are poor, and the flame retardant and mechanical properties of the TPE sheath material cannot be enhanced. Therefore, the TPE sheath material proposed by the present invention has the characteristics of low smoke, halogen-free, high-efficiency flame retardancy, and excellent oil resistance, and has broad application prospects in the industrial cable and new energy cable industries.

[0067] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, characterized in that: The preparation materials of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder at least include hexagonal boron nitride, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water and a silane coupling agent.

2. The modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder according to claim 1, characterized in that: The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.

3. A flame retardant, low smoke and oil resistant TPE sheath material, characterized in that: The ingredients of the flame retardant, low smoke and oil resistant TPE sheath material are measured in parts by weight and include: Thermoplastic elastomer 15-30 parts; Polypropylene 3-15 parts; 5-30 parts of white oil; 3-10 parts of the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder according to claim 1 or 2; Polyolefin elastomer 5-10 parts; 10-20 parts of organic flame retardant.

4. The flame-retardant, low-smoke and oil-resistant TPE sheath material according to claim 3, characterized in that: The thermoplastic elastomer is at least one of a styrene ethylene / butylene block copolymer and a hydrogenated styrene isoprene hydroxystyrene copolymer.

5. The flame-retardant, low-smoke and oil-resistant TPE sheath material according to claim 3, characterized in that: The white oil is at least one of 40#-300# industrial white oils.

6. The flame-retardant, low-smoke and oil-resistant TPE sheath material according to claim 3, characterized in that: The polyolefin elastomer is at least one of ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-butene copolymer and ethylene-octene copolymer.

7. The flame-retardant, low-smoke, and oil-resistant TPE sheath material according to claim 3, characterized in that: The organic flame retardant is at least one of a phosphorus-based flame retardant, a nitrogen-based flame retardant and a silicon-based flame retardant.

8. The flame-retardant, low-smoke, and oil-resistant TPE sheath material according to claim 3, characterized in that: The flame-retardant, low-smoke, and oil-resistant TPE sheath material further comprises 0.5-2 parts of a lubricant and 0.4-1 parts of an antioxidant, wherein the lubricant is at least one of fatty acids, aliphatic amides, metal soaps, and fatty alcohols, and the antioxidant is bis(octadecyl)hydroxylamine, tris[2,4-di-tert-butylphenyl]phosphite, pentaerythritol tetra(3-laurylthiopropionate), bis[3-[3-tert-butyl-4-hydroxy-5-methyl At least one of 1,5,8,12-tetrakis[4,6-bis(N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane and N-salicylicylamidophthalimide.

9. A method for preparing a flame-retardant, low-smoke, and oil-resistant TPE sheath material, characterized in that: The following steps are involved: Preparation of modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder: preparing modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder by a solution method using the hexagonal boron nitride described in claim 1 or 2, isopropanol, aluminum chlorohydrate, n-butanol, ammonia water, and a silane coupling agent; Preparation of flame-retardant, low-smoke and oil-resistant TPE sheath material: thermoplastic elastomer, polypropylene, white oil, modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder, polyolefin elastomer, organic flame retardant, lubricant and antioxidant are pre-mixed uniformly, and then mixed in an internal mixer to prepare a molten blend; the molten blend is granulated in a twin-screw-single-screw hot-cut air-cooled granulation unit, followed by secondary air cooling and vibration screening to finally obtain a flame-retardant, low-smoke and oil-resistant TPE sheath material.

10. The method for preparing the flame-retardant, low-smoke and oil-resistant TPE sheath material according to claim 9, characterized in that: The method for preparing the modified nano aluminum hydroxide / hexagonal boron nitride nano composite powder comprises the following steps: Hexagonal boron nitride is exfoliated to form hexagonal boron nitride nanosheets, which are then hydroxylated to obtain micro-nano hexagonal boron nitride powders. Nano-aluminum hydroxide is then in-situ grown on the surface of the micro-nano hexagonal boron nitride powders to obtain nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders. Subsequently, the nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders and a silane coupling agent are added to an ethanol solution, and the solution is subjected to ultrasonic dispersion and vacuum filtration and then dried to obtain modified nano-aluminum hydroxide / hexagonal boron nitride nano-composite powders.

11. A TPE sheath, characterized in that: The sheath is prepared by the preparation method of claim 7.